PENGARUH PENGGUNAAN LIMBAH KULIT KACANG HIJAU TERHADAP KONSUMSI PAKAN DAN PERTAMBAHAN BOBOT BADAN (PBB) KAMBING PERANAKAN ETAWA (PE) - Godfredus Budi (Jurnal Sains Peternakan, 2014)
This research purpose is to find out the effectiveness of adding the nutshell of greenpall on the woof of ettawa goat to increase the productivity. This research has done at Kepuh Gang X, Kelurahan Bandungrejosari Kecamatan sukun Kabupaten Malang on january to february 2012. The sample of this research is eight ettawa goats. The age of the subjects are eight months with 11-15 kg of weight. The cattles (ettawa goats) live in the corral experiment which completed with the woof place and drinking place too. The nutshell of greenpall is took from Gadang traditional market, Kabupaten Malang. The variable that observed is the woof consumption and the increasing weight of ettawa goat.The result of this research shows that the woof consumption for ettawa goat which added with nutshell of greenpall will have 469,89 g /tail/day, but the woof without adding the nutshell of greenpall with the resullt is 21,43 g /tail/day. And the other advatages to increase the weight of ettawa goat which add the nutshell of greenpall on the woof will have 92,86 g of weight/tail/day, but if there is no adding the nutshell of greenpall will have 21,43g of weight/tail/day. So,  it is necessary to add the nutshell of greenpall on the woof to get the good result of ettawa goat.